2022
DOI: 10.31557/apjcp.2022.23.1.253
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Ki67 Biomarker in Oral Submucous Fibrosis with Clinico-Pathological Correlations: A Prospective Study

Abstract: Objectives: Oral Submucous Fibrosis (OSMF) is potentially malignant disorder known to transform into oral cancer. The aim of this study is to determine the degree and pattern of expression of aberrant Ki67 in OSMF, oral squamous cell carcinoma (OSCC) and in normal oral mucosa patients (NOM). The objective is to correlate between Ki67 expression and degree of dysplasia in OSMF patents and also Ki67 expression with clinical and histological grading of OSMF and OSCC patient. Materials and Methods: A prospective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In their study, Kamala et al [ 68 ] observed an increase in Ki-67 expression with the severity of dysplasia. The Ki-67 antigen can be used as a marker for histological evaluations of OED.…”
Section: Discussion Of Potential Immunohistochemical Biomarkers In Gr...mentioning
confidence: 93%
See 2 more Smart Citations
“…In their study, Kamala et al [ 68 ] observed an increase in Ki-67 expression with the severity of dysplasia. The Ki-67 antigen can be used as a marker for histological evaluations of OED.…”
Section: Discussion Of Potential Immunohistochemical Biomarkers In Gr...mentioning
confidence: 93%
“…Ki-67-positive cells in well-differentiated OSCC were mainly located at the periphery of tumour nests; in moderately differentiated OSCC, they were located both at the periphery and in part of the centre of tumour nests, while they were scattered in the most poorly differentiated lesions. The study by Kamala et al [ 68 ] aimed to determine the degree and pattern of expression of aberrant Ki67 in OSMF. The study confirmed a statistically significant correlation between the expression of Ki-67 with the clinical and histological grading of OSMF and the histological grading of OSCC.…”
Section: Discussion Of Potential Immunohistochemical Biomarkers In Gr...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that Ki67 functions somewhat like a surfactant, facilitating chromosome movement and interacting with the mitotic spindle to prevent the collapse of chromosomes into a chromatin mass after the disassembly of the nuclear membrane [39]. Ki67 serves as a marker of cell proliferation [40], and multiple experiments have confirmed its presence in the S-phase, G2-phase, and M-phase, except for the G0-phase [41]. However, there is variability in the expression of the Ki67 antigen during the G1 phase [42].…”
Section: A Potential Protein Biomarker Ki67mentioning
confidence: 99%